2011
DOI: 10.1007/s12010-011-9347-3
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Phlorotannins from Eisenia bicyclis and Their Hepatoprotective Effect against Oxidative Stress Induced by tert-Butyl Hyperoxide

Abstract: Eisenia bicyclis (Kjellman) Setchell is a common brown alga that inhabits the middle Pacific coast around Korea and Japan. In this study, the ethanol extract and its serial solvent fractions were prepared from fresh E. bicyclis, and their hepatoprotective effects were investigated against hepatotoxicity in tert-butyl hyperoxide(t-BHP)-injured HepG2 cells. When these samples were used at a dose of 10-40 μg/mL⁻¹, they significantly protected the t-BHP-induced cell death in HepG2 cells. Among fractions, ethyl ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 27 publications
3
35
0
Order By: Relevance
“…Ethyl acetate has been widely used to selectively extract polyphenolic compounds from various seaweeds [8,23,24,25,26,27,28]. TPC in the ethyl acetate fraction of S. fusiforme was similar to that of Fucus vesiculosus (88.3 ± 2.2 mg PGE/100 mg) reported by Wang et al [1], but dramatically higher than that of many other species including Eisenia bicyclis [29,30,31], Ecklonia maxima [32], and S. muticum [4]. The present study showed that it was also effective in enriching phlorotannins from the crude extract of S. fusiforme .…”
Section: Resultsmentioning
confidence: 81%
“…Ethyl acetate has been widely used to selectively extract polyphenolic compounds from various seaweeds [8,23,24,25,26,27,28]. TPC in the ethyl acetate fraction of S. fusiforme was similar to that of Fucus vesiculosus (88.3 ± 2.2 mg PGE/100 mg) reported by Wang et al [1], but dramatically higher than that of many other species including Eisenia bicyclis [29,30,31], Ecklonia maxima [32], and S. muticum [4]. The present study showed that it was also effective in enriching phlorotannins from the crude extract of S. fusiforme .…”
Section: Resultsmentioning
confidence: 81%
“…According to de Oliveira e Silva et al (2012), a pre-treatment with polyphenol rich fractions from Halimeda opuntia led to reductions in serum and liver TBARS. Kim et al (2011) also observed a comparable reduction in hydroperoxide levels in the liver, relative to the CCl 4 -treated group, in a study of rats fed on Saengshik, a non-cooked food containing vegetables and seaweeds.…”
Section: Antioxidant Activity Protecting Against Liver Damage In CCL mentioning
confidence: 67%
“…When comparing different fractions from the seaweed Eisenia bicyclis (Phaeophyceae), Kim et al (2011) found that the highest phenolic content was associated with the antioxidant activity and the hepatoprotective effect, against tert-butyl hyperoxide damage (t-BHP) in hydrophilic fractions from the seaweed.…”
Section: Phenolic Contentmentioning
confidence: 99%
“…Recent studies that have focused on the biological and pharmacological activity of seaweeds have shown them to be potentially prolific sources of highly bioactive secondary metabolites that might represent useful leads in the development of new pharmaceutical agents [28]. Several varieties of bioactive novel compounds such as phlorotannins, diterpenes, polysaccharides, phytosterols and phytopigments from seaweeds have been isolated; moreover, many of these compounds have been demonstrated to possess numerous biological activity, including hepatoprotective activity [13,16,29]. Individual phlorotannins isolated from the active EtOAc fraction of the MeOH extract of the edible brown algae E. stolonifera and E. bicyclis have been reported to exert strong hepatoprotective activity in tacrine‐ and t ‐BHP‐treated HepG2 cells, respectively [13,16].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have investigated the hepatoprotective effects of the brown algae Ecklonia stolonifera and Eisenia bicyclis on t ‐BHP‐ and tacrine‐treated HepG2 cells. In particular, researchers have been interested in the polar EtOAc and n ‐BuOH fractions derived from these algae, and have identified their individual polar phlorotannin components, including dioxynodehydroeckol, phlorofucofuroeckol A, eckol and 2‐phloroeckol as effective hepatoprotective agents via an activity‐guided fractionation strategy [13,16,17]. In addition to these various polar hepatoprotective components derived from seaweeds, fucosterol, which has been isolated from the nonpolar fractions of the marine alga Pelvetia siliquosa , was also found to be an intriguing nonpolar candidate that exerted hepatoprotective effects in CCl 4 ‐intoxicated rats [18].…”
Section: Introductionmentioning
confidence: 99%